Thyroid profile in newly diagnosed male HIV patients: a study from North Western part of India - Midha, Naresh Kumar; M., Chaudhary; K., Choudhary L.; S., Srivastva; M., Gupta (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this study was to determine proportion of newly diagnosed male HIV cases with thyroid dysfunction at different levels of CD4 counts. Methods: 195 newly diagnosed male HIV patients attending medical OPD, ART centre and medical wards of SMS Medical College and Hospital, during a period of May 2012 to April 2013 were enrolled in the study. These patients were divided in three groups on the basis of CD4 cell counts. Group A: CD4 counts <200/mm3, Group B: CD4 counts 200-499/mm3 and Group C: CD4 counts >500/mm3. Results: We concluded a negative correlation between the CD4 counts and serum TSH level (r = -0.382) which was significant (p-value <0.05). Overall 32 (16.41%) patients had increased TSH, 4 (2.05%) patients had decreased and 159 (81.53%) patients had normal TSH level. Plasma TSH values in group A were higher than group B and C and they were highly significant (p<.001). Mean plasma TSH values in patients of group A, B and C was 4.56±3.60 µIU/mL (range: 1.10-17.74), 2.20±1.02 µIU/mL (range:0.24-4.22) and 2.23±1.06 µIU/mL (range:0.28-4.25) respectively. (Reference normal value = 0.4-4.0 µIU/mL). There was significantly positive correlation (p-value < 0.01) found between the CD4 counts and serum free T4 levels (r = +0.378). Conclusions: This study has demonstrated a high prevalence of thyroid dysfunction in HIV infected patients of this part of country. High prevalence of thyroid dysfunction may contribute to the morbidity of the patients and have a bearing on quality of life of the HIV infected patients. Severity of hypothyroidism was correlated with decreasing CD4 cell count.